2012
DOI: 10.1029/2011jd016848
|View full text |Cite
|
Sign up to set email alerts
|

Wind‐induced splash in Class A evaporation pan

Abstract: [1] This study investigates the wind-induced splash in the Class A evaporation pan through a series of wind tunnel experiments. The experimental results revealed that high wind speed can generate seiche wave inside the pan and splash water out of the pan in several minutes. The splash loss increases as the wind speed increases, and the loss rate is at least one order of magnitude greater than the evaporation rate. In other words, the water loss from the pan is not entirely due to evaporation, and the evaporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…According to him, pans that are installed in a way that represent the actual field conditions might produce accurate results, whereas the Class A Pan and other standard pans in use usually provide slightly inaccurate measured evaporation. Tanny et al [26] and Chu et al [27] conducted research related to the Class A evaporation pan and found that it is the least accurate method of measuring and estimating evaporation. All such limitations must be considered while dealing with evaporation estimates.…”
Section: Introductionmentioning
confidence: 99%
“…According to him, pans that are installed in a way that represent the actual field conditions might produce accurate results, whereas the Class A Pan and other standard pans in use usually provide slightly inaccurate measured evaporation. Tanny et al [26] and Chu et al [27] conducted research related to the Class A evaporation pan and found that it is the least accurate method of measuring and estimating evaporation. All such limitations must be considered while dealing with evaporation estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Low air humidity or less water vapor in the air allows more evaporation. Higher wind speed sweeps away more water from the waterbody to the atmosphere (Chu et al, 2012). Therefore, all these climatic factors significantly influence EP in any region.…”
Section: Discussionmentioning
confidence: 99%
“…A potential source of the difference could be the errors of the E pan data, including some extremely high values (Fig. 2 ), which are caused by multiple factors, such as intensive rain, high wind speeds 32 , and errors introduced while taking readings 33 , 34 . Also, K pan (0.77) used for E pan correction in this study is likely too small for some ecozones.…”
Section: Discussionmentioning
confidence: 99%